2006
DOI: 10.1016/j.jconrel.2005.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically controlled release of dexamethasone from conducting polymer polypyrrole coated electrode

Abstract: Chronic recordings from micromachined neural electrode arrays often fail a few weeks after implantation primarily due to the formation of an astro-glial sheath around the implant. We propose a drug delivery system, from conducting polymer (CP) coatings on the electrode sites, to modulate the inflammatory implant-host tissue reaction. In this study, polypyrrole (PPy) based coatings for electrically controlled and local delivery of the ionic form of an anti-inflammatory drug, dexamethasone (Dex), was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
393
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(412 citation statements)
references
References 58 publications
10
393
1
Order By: Relevance
“…Additionally, a drug delivery system should provide the drug locally, for example, making neuro-growth factors in the brain available to treat neurodegenerative conditions such as Parkinsons, Alzheimers and Huntingtons and to overcome the blood-brain barrier that prevents the drug entering the brain. It has been suggested that drug delivery systems can provide anti-inflammatory medicaments and growth factors directly into the local vicinity of the implant [31]. Another application is in bone and tissue engineering where growth factors can be locally delivered at high concentrations with precise control [32][33][34].…”
Section: General Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a drug delivery system should provide the drug locally, for example, making neuro-growth factors in the brain available to treat neurodegenerative conditions such as Parkinsons, Alzheimers and Huntingtons and to overcome the blood-brain barrier that prevents the drug entering the brain. It has been suggested that drug delivery systems can provide anti-inflammatory medicaments and growth factors directly into the local vicinity of the implant [31]. Another application is in bone and tissue engineering where growth factors can be locally delivered at high concentrations with precise control [32][33][34].…”
Section: General Drug Delivery Systemsmentioning
confidence: 99%
“…By applying a negative potential, the polymer film is reduced and its cationic charge is neutralised, which causes the ejection of the anionic drug by electrostatic force synchronised with the ingress of hydrated cations into the polymer bulk. This leads to the film swelling [31,58]. However, holding the film under a negative stimulus potential for a period of time can cause the film to lose its electrical conductivity which is not always possible to recover [31].…”
Section: Drug Deliverymentioning
confidence: 99%
“…They have been used for bio-sensing [5][6][7], as electrodes for stimulation or recording [8,9], for controlling cell adhesion, proliferation [10][11][12] and stem-cell differentiation [13], for controlled drug release [14,15] and even to mechanically stimulate cells [16]. They can be fabricated electrochemically using various counter ions [17,18] and modified with a variety of biomolecules [5,6,19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group extended the application of PPy nanowire network to this field, obtaining an effective drug release system with high adenosine triphosphate (ATP) release efficiency [5]. 2 It is well known that CPs can be used as drug carriers due to their unique dopingdedoping and stimulus-responsive property [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], where drugs can be incorporated into CPs as dopants and then be released upon electrical stimulation. Therefore, the capacity of drug loading is dependent on the doping level (which is usually low) and the type of drugs is restricted to the charged and small molecules.…”
Section: Introductionmentioning
confidence: 99%